2022
DOI: 10.1007/s15010-022-01777-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with anti-SARS-CoV-2 monoclonal antibodies in pregnant and postpartum women: first experiences in Florence, Italy

Abstract: Purpose Pregnant and postpartum women are at increased risk of developing severe COVID-19. Monoclonal antibodies (mAbs) are now widely used in high-income countries to treat mild to moderate COVID-19 outpatients at risk for developing severe disease. Very few data are available on the use of mAbs in special populations, including pregnant and postpartum women. Here we present our early experience with mAbs in these two populations. Methods Electronic recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…We identified 53 articles, 28 of which were assessed with respect to their eligibility for inclusion and 17 studies ultimately included in the systematic review ( Table 1 , Figure 1 ) [ 30 , 32 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Eight studies came from the United States of America (USA), four from Europe, three from Japan and the other two studies were from the United Arab Emirates (UAE).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 53 articles, 28 of which were assessed with respect to their eligibility for inclusion and 17 studies ultimately included in the systematic review ( Table 1 , Figure 1 ) [ 30 , 32 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Eight studies came from the United States of America (USA), four from Europe, three from Japan and the other two studies were from the United Arab Emirates (UAE).…”
Section: Resultsmentioning
confidence: 99%
“…However, for preventive purposes, pregnant women have been included among the risk categories for major consequences of a related COVID-19 infection [ 1 , 2 , 3 , 4 , 5 , 6 ]. Furthermore, pregnant women have been excluded from clinical pharmaceutical trials of new drugs to be used against the virus, resulting in poor documentation of the complications and consequences of infection during pregnancy [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Nonetheless, the results of some studies showed that COVID-19 infection during pregnancy was associated with a greater probability of maternal, fetal, and neonatal adverse events [ 14 , 15 , 16 ], as more cases of preeclampsia, hospitalization in intensive care, preterm birth, and neonatal mortality were recorded compared to pregnant women not affected by the virus [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms 2023,11, 1953. https://doi.org/10.3390/microorganisms11081953 https://www.mdpi.com/journal/microorganisms…”
mentioning
confidence: 99%
“…[3][4][5][6] Yet, no studies evaluate the effectiveness of mAbs targeting SARS-CoV-2 among pregnant persons, data are limited on the safety of mAbs in pregnancy, and immunoglobulin-based therapy remains controversial. [7][8][9][10][11][12][13] The purpose of this study is to estimate the rate of drug-related adverse events from mAb treatment among a cohort of pregnant persons with SARS-CoV-2 infection, the rate of obstetric-associated safety outcomes among all persons who delivered, and the risk-adjusted association between mAb treatment and composite 28-day COVID-19-related hospital admission or emergency department (ED) visit, COVID-19-associated delivery, or mortality compared to no mAb treatment.…”
Section: Introductionmentioning
confidence: 99%